2019
DOI: 10.3390/ijerph16142461
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Parental Socialization Styles, Empathy and Connectedness with Nature: Their Implications in Environmentalism

Abstract: Parents exert a strong influence on several adjustment outcomes. However, little is known about their influence on adolescents’ connectedness with the environment. This study examined the relationships between parenting styles, empathy and connectedness with the environment. The two-dimensional socialization model was used with four resulting styles: Indulgent, authoritative, neglectful and authoritarian. The sample comprised 797 adolescents (52.7% girls) from six public secondary schools who were aged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 167 publications
(226 reference statements)
1
30
0
3
Order By: Relevance
“…Another aspect of demonstrated importance for adolescent psychosocial adjustment is parental socialization [29,30]. Traditionally, the relationship between parenting style and child adjustment has been analyzed following a two-dimensional orthogonal model of parental socialization, labeled as involvement/acceptance and strictness/imposition [31].…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of demonstrated importance for adolescent psychosocial adjustment is parental socialization [29,30]. Traditionally, the relationship between parenting style and child adjustment has been analyzed following a two-dimensional orthogonal model of parental socialization, labeled as involvement/acceptance and strictness/imposition [31].…”
Section: Introductionmentioning
confidence: 99%
“…This dysfunction may cause elevated psychopathic traits, which may lead to antisocial or violent behaviors [5]. Parenting styles have proven to be a very important factor in the family of origin environment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of good parenting styles in the family of origin is very important in preventing juvenile delinquency [9]. At present, the main problems in the parenting style of families are the degree of supervision and discipline of parents and whether they can give enough care and encouragement to their children [7]. At the same time, many studies have shown that a positive parent-adolescent relationship protects adolescents against delinquency [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations